PHR기반 개인 맞춤형 식이·운동 관리 서비스 개발 - 정은영(Eun-Young Jung); 정병희(Byoung-Hui Jeong); 윤은실(Eun-Sil Yoon); 김동진(Dong-Jin Kim); 박윤영(Yoon-Young Park); 박동균(Dong-Kyun Park) (韓國컴퓨터情報學會論文誌, 2012)
We developed a Smartphone application based on PHR(Personal Health Records) provided by a tertiary hospital to provide users personalized diet, exercise contents. It uses Relevance ratio algorithm of diet and excercise being correlated with diseases listed on PHR to provide personalized contents to management of individual diseases and record the amounts of food taken and exercise along with calories consumed through exercise. Besides, developed U-Health Service also considering users' conditions and conveniences, as a service to use contents and record suitable for the individuals who share the information on restaurants locations, their menus, and nutrition based on users' location information. 개인 맞춤형 식이 운동 콘텐츠 제공을 위해 1개 3차병원에서 제공하는 PHR(Personal Health Records)을 기반으로 건강관리 스마트폰 어플리케이션을 개발하였다. PHR의 상병명에 근거하여 각 질환과의 상관관계를 적용한 식이 운동 적합률 알고리즘을 통해 개인의 질환을 관리하기 위한 맞춤형 콘텐츠를 제공하며, 식사량과 운동량을 기록하여 섭취 소비한 칼로리를 기록하는 기능을 제공한다. 또한 사용자의 위치정보를 근거로 한, 음식점 위치 정보 및 해당 메뉴, 그에 따른 영양분석에 대한 정보를 제공하는 개인에게 적합한 콘텐츠를 이용하고 기록할 수 있는 서비스로써, 사용자의 상태와 편의성을 고려하여 유헬스 서비스를 제공할 수 있다.